Pengembangan Metode Mendongeng Menggunakan Multimedia untuk Meningkatkan Kemampuan Bahasa Anak Kelompok B di TK Rinjani Unram Tahun Pelajaran 2020/2021 - Nurhasanah Nurhasanah; Baik Nilawati Astini; Fahruddin Fahruddin; Yundia Pratiwi Nengsi (Indonesian Journal of Elementary and Childhood Education, 2021)
The purpose of this study was to determine the development of storytelling methods using multimedia to improve language skills, especially listening and speaking skills in children group B at TK Rinjani Unram in the 2020/2021 academic year. This type of research is development research, with three stages of development consisting of planning, implementation, observation, and development analysis. The subjects of this study were 10 children group B. Data collection methods used in this research are observation and documentation methods. Data analysis was carried out descriptive qualitatively. The development of storytelling methods using multimedia to improve the language skills of children group B is carried out with steps such as: (1) the preparation stage, (2) the stage opening, (3) the stage of implementing the process of watching a fairy tale (4) the stage of watching a fairy tale. The results of the research obtained by the researcher at the development stage I obtained an average result of 40.16%, at the second development stage the average result was 62.66% and in the third development stage the achievement of language skills development in children group B. reached 88.33%. The conclusion is that language skills, especially listening and speaking skills in children group B in TK Rinjani Unram can be improved through the development of storytelling methods using multimedia which are carried out repeatedly by always making improvements at each stage of development.